Bonding All-Ceramic Restorations with Two Resins Cement Techniques: A Clinical Report of Three-Year Follow-Up - Anchieta, Rodolfo Bruniera; Rocha, Eduardo Passos; Almeida, Erika Oliveira de; Freitas Junior, Amilcar Chagas; Martini, Ana Paula (European Journal of Dentistry, 2011)
Ceramics have been widely used for esthetic and functional improvements. The resin cement is the material of choice for bonding ceramics to dental substrate and it can also dictate the final esthetic appearance and strength of the restoration. The correct use of the wide spectrum of resin luting agents available depends on the dental tooth substrate. This article presents three-year clinical results of a 41 years old female patient B.H.C complaining about her unattractive smile. Two all-ceramic crowns and two laminates veneers were placed in the maxillary incisors and cemented with a self-adhesive resin luting cement and conventional resin luting cement, respectively. After a three-year follow-up, the restorations and cement/teeth interface were clinically perfect with no chipping, fractures or discoloration. Proper use of different resin luting cements shows clinical appropriate behavior after a three-year follow-up. Self-adhesive resin luting cement may be used for cementing all-ceramic crowns with high predictability of success, mainly if there is a large dentin surface available for bonding and no enamel at the finish line. Otherwise, conventional resin luting agent should be used for achieving an adequate bonding strength to enamel. (Eur J Dent 2011;5:478-485)
Keywords: Conventional resin luting agent; Self-adhesive resin luting cement; Dental ceramic